The human semantic potential : spatial language and constrained connectionism - Regier, Terry (Neural network modeling and connectionism. A Bradford Book, 1996)
The linguistic categorization of space Connectionism and cognitive models Learning without explicit negative evidence Structures A model of spatial semantics